Medical research at universities – An international comparison - Rainer Frietsch; Peter Neuhäusler; Carolin Michels; Friedrich Dornbusch (Expertenkommission Forschung und Innovation (EFI), 2014)
This study compares the publication and patent performance of selected medical research locations in five countries. The bibliometric indicators reveal that mostly the U.S. locations, above all Harvard University, have the highest score in the rankings in terms of quantity and quality of their research output. On average, the German research locations score in the medium ranks when it comes to the number of publications and publication intensities. Medical research in Munich and Hanover, however, achieves top scores in publications per capita, and thus can be seen as highly productive. Yet, the citation indicators show that the scientific profiles of German universities in medical research differ. While on average the locations Hanover, Berlin and Munich target internationally less visible journals, and reach high citation rates there. Heidelberg and Tubingen are more internationally oriented, where it is harder to achieve high scientific regard values. The differences can mainly be explained by differences in the subdisciplines of medical research, which are more or less internationally oriented and therefore also reach higher or lower citation numbers.
Keywords: 330; Medizin; Patent; Zitationsanalyse; Bibliometrie; Internationaler Wettbewerb; Welt